Construction estimate made easy / from conquistador to Chicanos - Meier, Matt S.; Ribera, Feliciano (Canada : Harper & Row Publishers, Inc., 1993)
[This text] includes expanded chapters on [the] new developments of the recent past: the Chicano Movimiento of the late sixties and seventies; their considerable political and economic achievements; improvements in immigration law; the creative explosion in literature and the fine arts; the increased role of Chicanas; the rise and decline of four great leaders - Cesar Chavez, "Corky" Gonzales, Reies Lopez Tijerina, and José Angel Gutierrez. An extensive account of the pre-Columbian world and the impact of the early Spanish explorers and settlers takes note of new findings and interpretations. -Back cover
The Meeting of two worlds -- Revolution and disarray -- Man and land on the frontier -- Manifest destiny -- Roots of the poison -- Culture and conflict in new Mexico -- North from Mexico -- Mande Vd., Senor -- Deporting Jesus -- Unwanted Mexicans -- Heroes second class -- Braceros : World War II and after -- The Slaves we rent : undocumenteds, green carders, commuters -- A new breed -- El Movimiento -- The Chicano cultural renaissance -- Jobs, business, and politics -- Epilogue
Includes index.
Keywords: MEXICAN AMERICANS -- HISTORY